Urbanization Challenges In Cipinang Besar Utara: A Study On Slum Conditions And Mitigation - Andryansyah, Muhammad; Jayady, Arman (International Journal Labs, 2023)
Urban regions across the globe have a multitude of issues arising from the presence of slums, which are further intensified by the rapid process of urbanization. The exponential growth of informal settlements has detrimental effects on the well-being of the populace and hinders socio-economic advancement. This paper examines these challenges in Cipinang Besar Utara sub-district, East Jakarta, DKI Jakarta Province-Indonesia, which is also one of the main growth centers in Indonesia. This study aims to assess the level of slum settlement conditions in accordance with the Regulation of the Minister of Public Works and Public Housing Number 14 of 2018 (Permen-PUPR No.14/RT/M/2018). The research proceeded through five stages: data collection, questionnaire design, data collection for slum settlement assessment, valuation calculations, and strategy formulation. Direct observation and interviews built on the existing profile and informed the questionnaire design. Data collected from questionnaires, assisted by local representatives, facilitates the assessment of slums against regulatory guidelines. The results of the study show that RW 12 is a non-slum area, while RW 01, RW 04 to RW 11, RW 13 and RW 14 are categorized as mild slum areas. In addition, RW 02 and RW 03 are classified as moderate slums. The suggested mitigation strategy is in accordance with Permen-PUPR No. 14/RT/M/2018, offers recommendations to address slum conditions. This study provides insights to limit the development of slum settlements in North Cipinang Besar Sub-district, contributing to its environmental improvement. This finding has implications for broader urban development policies in DKI Jakarta Province and its surroundings.